Peranan Ibnu Mujāhid dalam Ilmu Qira’at - Ahsin Sakho Muhammad (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
In the history of the development of the Science of Qiraat, it is known that the writing of this science began as early as the first century. Then, in the following centuries, the writing became more prolific, especially in the fourth and fifth centuries of the Hijrah. This was the golden age of the Science of Qiraat. After that, from the sixth to the eighth centuries, the science of Qiraat experienced stagnation. Amidst the numerous differences in the field of Qiraat, many people were perplexed by this phenomenon. This can be seen from the abundance of books that no longer distinguish between mutawatir and non-mutawatir Qiraat. It was Dūrīng this time that Ibn Mujāhid emerged to calm the community by gathering Qiraat that were truly mutawatir and believed to be valid. The development of the Science of Qiraat in the past cannot be separated from the role of Ibn Mujāhid (245-324 H). He was the first initiator of crystallizing the Qiraat into seven, which eventually became known as the Seven Qiraat. This paper will discuss the role of Ibn Mujāhid in the Science of Qiraat.